Advances in luminescence-based technologies for drug discovery. (2nd January 2023) - Baljinnyam, Bolormaa; Ronzetti, Michael; Simeonov, Anton
ABSTRACT: Introduction: Luminescence-based technologies, specifically bioluminescence and chemiluminescence, are powerful tools with extensive use in drug discovery. Production of light during chemiluminescence and bioluminescence, unlike fluorescence, doesn't require an excitation light source, resulting in high signal-to-noise ratio, less background interference, and no issues from phototoxicity and photobleaching. These characteristics of luminescence technologies offer unique advantages for experimental designs, allowing for greater flexibility to target a wide range of proteins and biological processes for drug discovery at different stages. Areas covered: This review provides a basic overview of luciferase-based technologies and details recent advances and use cases of luciferase and luciferin variations and their applicability in the drug discovery toolset. The authors expand upon specific applications of luciferase technologies, including chemiluminescent and bioluminescent-based microscopy. Finally, the authors lay out forward-looking statements on the field of luminescence and how it may shape the translational scientists' work moving forward. Expert opinion: The demand for improved luciferase and luciferin pairs correlates strongly with efforts to improve the sensitivity and robustness of high-throughput assays. As luminescent reporter systems improve, so will the expansion of use cases for luminescence-based technologies in early-stage drug discovery. With the synthesis of novel, non-enzymatic chemiluminescence-based probes, which previously were restrained to only basic research applications, they may now be readily implemented in drug discovery campaigns.